Pengembangan Media Pembelajaran Berbasis Website Untuk Meningkatkan Hasil Belajar Kognitif Peserta didik - Saprudin, Saprudin; Pratama, Anggi Tias (Universitas Negeri Jakarta, 2025)
This study examines the effect of website-based learning media on students' cognitive learning outcomes in class X Biology subjects. Using a quantitative research design with the Pretest-Posttest Control Group Design model, this study involved 72 SMA Negeri 10 South Konawe, Southeast Sulawesi Indonesia students, who were divided into experimental and control groups. The experimental group used website-based learning media, while the control group used PowerPoint media. The results showed a significant increase in the average value of cognitive learning outcomes in the experimental group compared to the control group, with an average N-Gain value of 0.36 (medium criteria) and 0.20 (low criteria), respectively. The use of website-based learning media proved to be more effective in improving learning outcomes because it was able to increase learner involvement, flexibility, and learning independence.